2014
DOI: 10.1111/exd.12422
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum HMGB1 levels in patients with Henoch–Schönlein purpura

Abstract: High-mobility group box-1 (HMGB1) has been implicated as a pro-inflammatory cytokine in the pathogenesis of various inflammatory and autoimmune diseases. However, information about HMGB1 in Henoch-Schönlein purpura (HSP) is still unclear. Herein, we investigated the role of HMGB1 in patients with HSP and the pro-inflammatory effects of HMGB1 on human dermal microvascular endothelial cell line (HMEC-1). Serum HMGB1 levels in patients with HSP together with patients with allergic vasculitis (AV) and urticarial v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…had reported that the mitogenic and chemotactic activities of HMGB1 can be inhibited by glycyrrhizin. Also, glycyrrhizin can bind directly to HMGB1 protein and confirm its binding site . Additionally, glycyrrhizin has been recognized as a HMGB1 inhibitor and potentially blockade the extracellular release of HMGB1 from the cell nucleus .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…had reported that the mitogenic and chemotactic activities of HMGB1 can be inhibited by glycyrrhizin. Also, glycyrrhizin can bind directly to HMGB1 protein and confirm its binding site . Additionally, glycyrrhizin has been recognized as a HMGB1 inhibitor and potentially blockade the extracellular release of HMGB1 from the cell nucleus .…”
Section: Discussionmentioning
confidence: 87%
“…Also, glycyrrhizin can bind directly to HMGB1 protein and confirm its binding site. 23,24 Additionally, glycyrrhizin has been recognized as a HMGB1 inhibitor and potentially blockade the extracellular release of HMGB1 from the cell nucleus. 15,25 In East Asia, glycyrrhizin has been recognized as a natural anti-inflammatory agent and now extensively used for the treatment of various inflammatory skin diseases including psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, HMGB1 has been well recognized as an important signaling molecule involved in both acute and chronic inflammation process . Its expression was significantly increased in a variety of skin diseases, such as psoriasis, alopecia areata, vitiligo, atopic dermatitis, Henoch‐Schönlein purpura (HSP), pemphigus, and drug‐induced hypersensitivity syndrome/drug reaction with eosinophilia and systemic symptoms (DRESS) . Due to the similar pharmacological efficacy to corticosteroids but with milder side effects, Glycyrrhizin has been widely utilized in several dermatologic disorders for many years, such as active‐stage generalized vitiligo, psoriasis, alopecia areata, and is also reported to be effective in alleviating the symptoms of atopic dermatitis and systemic sclerosis in animal model .…”
Section: Discussionmentioning
confidence: 99%
“…It has been proven in our previous study that HMGB1 is involved in the pathogenesis of inflammatory and autoimmune disorders, such as, Henoch– Schonlein purpura (HSP), allergic vasculitis (AV), and urticarial vasculitis (UV). It also altered HMGB1 distribution in lesional skin in patients with HSP ( 11 13 ). However, the function and mechanism of HMGB1 in vasculitis has not been clearly stated.…”
Section: Introductionmentioning
confidence: 97%